Advances in the treatment of rotator cuff tears: Management of rotator cuff tears in the athlete - Reinholz, A. K.; Till, S. E.; Arguello, A. M.; Barlow, J. D.; Okoroha, K. R.; Camp, C. L. (Clinics in Sports Medicine, 2023)
• Rotator cuff tears in overhead athletes are commonly partial-thickness articular-sided tears; of these, most can be successfully treated with nonoperative management. • Structured rehabilitation focusing on all parts of the kinetic chain is key. • Surgical debridement and repair of concomitant pathology may allow players to return to sport, though outcomes are highly variable. • Repair is generally reserved for athletes failing nonoperative management or those with acute, full-thickness tears. • When repair is indicated, double-row transosseous equivalent is the preferred repair technique for most athletes, but in overhead athletes, this is performed in a lateralized location within the anatomic footprint.